Transformational, transactional leadership and rational decision making in services providing organizations: Moderating role of knowledge management processes - Muhammad Naveed Riaz; Muhammad Tahir Khalili (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The study is based on moderating role of knowledge management processes in the relationship between transformational, transactional leadership and rational decision making in services providing organizations. The study also examined the effect of transformational leadership and knowledge management processes on the predication of rational decision making. Information from services providing organizations including banks, hospitals, and universities is collected through Multifactor Leadership Questionnaire, Knowledge Management Process Scale and General Decision Making Styles Questionnaire. A purposive sample of 1200 employees participated in the present study. Moderated Regression analysis confirmed that transformational, transactional leadership and knowledge management processes positively predicted rational decision making. Finally, knowledge management processes moderated between transformational, transactional leadership and rational decision making.
Keywords: 330; transformational-transactional leadership; knowledge management processes; rational decision making